2018
DOI: 10.1016/j.bbcan.2018.05.006
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs as potential liquid biopsy biomarkers in colorectal cancer: A systematic review

Abstract: Emerging evidence has demonstrated the feasibility of circulating miRNAs as robust non-invasive biomarkers for the diagnosis in colorectal cancer. The use of circulating miRNAs for the early detection of colorectal cancer (CRC) is of particular interest as it can offer a potential complementary approach to screening colonoscopy. However, the development of circulating miRNAs as "liquid biopsy" biomarkers for development into clinical screening tests has been hampered by several issues. In this article, we summ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
63
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 78 publications
1
63
0
Order By: Relevance
“…Sequencing miRNAs from plasma was not sufficiently established. Our experience with plasma circulating miRNAs enabled us to develop specific operating procedures for the pre‐analytical phase that ensure the reproducibility of data . The operating procedures were shared with the other hospitals participating in the external validation phase.…”
Section: Discussionmentioning
confidence: 99%
“…Sequencing miRNAs from plasma was not sufficiently established. Our experience with plasma circulating miRNAs enabled us to develop specific operating procedures for the pre‐analytical phase that ensure the reproducibility of data . The operating procedures were shared with the other hospitals participating in the external validation phase.…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs, one kind of small noncoding RNA molecules, possess important functions on regulating gene expression and biological processes . Previous many researchers found that the tumorigenesis was correlated with the expression change of miRNAs, suggesting that miRNAs were hopeful to be novel biomarkers used for the diagnosis and treatment of colorectal cancer . For examples, miR‐21 took part in the multiple processes of colorectal tumorigenesis, not only via regulating MAPK pathway but also via linking with Wnt/β‐catenin signaling; miR‐135 family and miR‐34 family that contacted with Wnt signaling pathway have been proved they played key roles in the development of colon cancer .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is necessary to identify and develop more biomarkers, which contributes to the earlier detection of colorectal cancer. In most cases, colorectal cancer was developed from premalignant colorectal adenomas that gradually accumulated many mutations, further led to epigenetic alterations and finally became malignant . Previous research reported that mutations of APC and KRAS might lead to colorectal cancer .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations